Die ehemaligen Territorien des Deutschen Reiches in ihrer kulturlandschaftlichen Bedeutung - Huttenlocher, Friedrich (ERDKUNDE, 1957)
Amongst the forces which have shaped the German cultural landscape first place is taken by the organizing forces which act by way of the economy, and the economic attitude which is closely connected with it. These stem in most cases from an original stratum of the 17 th and 18th centuries. The modern period is characterized by the beginning of rationalism, the Reformation and Counter-Reformation, absolutism, the start of a civil service type administration with its tendencies towards uniformity and centralization, and the expansion of industries due to the principles of mercantilism. The acceptance of these new ideas in the numerous territories of Germany differed greatly and depended on the kind of territory; whether it was ecclesiastical or secular and whether it was large or small. In this process a regularity may be found in the reaction against the new era. As a result it is possible to distinguish territorial types whose chequered mosaic forms until today the main characteristic of the German cultural landscape. Following from the pronounced fragmentation into territories of different denominations these contrasts are tangible in Rhenish Germany and especially in the South West; this is shown in more detail in the section devoted to the characterization of individual types. Amongst these, two main groups may be distinguished. There are firstly those, in the majority ecclesiastical territories, which retained their faith and social structure. Of the secular rulers the same attitude was shown by the Habsburgs with their extensive but greatly dispersed possessions. The Wittelsbachs in the Electorates of Bavaria and the Palatinate behaved similarly. Characteristic of their territories was the small degree of compactness and the frequent occurrence of landed country gentry. Special positions in this conservative group of territories were occupied by the Imperial Knights and the Imperial cities. The other contrasting group consisted of the large territories of protestant denomination. Their purposeful endeavours to form compact territories led to the displacement of the landed gentry, and ecclesiastical and administrative centralization and uniformity. Support of manufacture by the state finally led to industrialization over wide areas, overpopulated in terms of agriculture, and took away the special legal and economic position which the towns had enjoyed so far. A varying intermediate position between individualized and the centralized territories was occupied by the smaller territories of the high nobility. In most cases they followed the example of their larger neighbours.